2005
DOI: 10.1042/cs20040177
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of blood flow and post-occlusive reactive hyperaemia as measured by venous occlusion plethysmography

Abstract: Venous occlusion plethysmography is commonly used as a tool to assess BF (blood flow) and VR (vascular resistance) at baseline and during PORH (post-occlusive reactive hyperaemia). However, little is known about the reproducibility of this method. The purpose of the present study was to investigate short- (hours) and medium (week)-term reproducibility of forearm, calf and thigh BF and VR at baseline and during PORH. Reproducibility was assessed by the CV (coefficient of variation). In eight subjects, baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 42 publications
10
60
1
3
Order By: Relevance
“…Leg blood flow (in ml/min per dl of leg tissue) was calculated as the slope of the volume change curve over a 4-second interval, starting directly after the inflation-induced cuff artifact (2 seconds). 21 Thigh vascular resistance was calculated as the mean arterial pressure (mm Hg) divided by thigh blood flow (in ml/min/dL) and expressed in arbitrary units (AU; mm Hg/mL/min/dL). Because of the differences in baseline vascular characteristics between SCI and control subjects, analysis of absolute values could affect the comparison between both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg blood flow (in ml/min per dl of leg tissue) was calculated as the slope of the volume change curve over a 4-second interval, starting directly after the inflation-induced cuff artifact (2 seconds). 21 Thigh vascular resistance was calculated as the mean arterial pressure (mm Hg) divided by thigh blood flow (in ml/min/dL) and expressed in arbitrary units (AU; mm Hg/mL/min/dL). Because of the differences in baseline vascular characteristics between SCI and control subjects, analysis of absolute values could affect the comparison between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…20 A mercury-in-silastic strain gauge (Hokanson Inc) was placed at mid-thigh, at least 10 cm above the patella and at least 4 cm below the cuff. 21 The lower legs were supported Ϸ10 cm above heart level to facilitate venous outflow between the venous occlusion periods.…”
Section: Protocolmentioning
confidence: 99%
“…We have previously shown that the reproducibility of upper leg blood flow measurements is good (Thijssen et al 2005a). The thigh cuffs were simultaneously inflated to 50 mmHg using a rapid cuff inflator (Hokanson E-20, D.E.…”
Section: Methodsmentioning
confidence: 99%
“…Coefficient of variation was calculated for the FMD% responses in the noncuffed arm for each intervention day. 26 …”
Section: Statisticsmentioning
confidence: 99%